Inuit principals and the changing context of bilingual education in Nunavut - Tulloch, Shelley; Metuq, Lena; Hainnu, Jukeepa; Pitsiulak, Saa; Flaherty, Elisapee; Lee, Cathy; Walton, Fiona (Études/Inuit/Studies, 2016)
Although positive policies and laws promote the Inuit language and Inuit qaujimajatuqangit (IQ) in all sectors of Nunavut society, including at all levels of Inuit schooling, many Nunavut schools are still struggling to overturn colonizing practices and mindsets that have hindered effective education of Inuit youth. In this article, we document perceptions of students, teachers, principals, parents, and community members related to school transformation under the leadership of an Inuk principal and and Inuk co-principal in two Nunavut high schools. These oral accounts show that having an Inuit principal enhanced students’ opportunities to learn and practise the Inuit language and IQ through enhanced, localized programming and increased exposure to Inuit ways of speaking and being. Parents were mobilized and equipped to support and advocate for their children, including joining local District Education Authorities, when they were able to communicate easily and effectively with the principal, and saw their knowledge, culture, and language valued and practised in the school system. We argue that the strong, community-anchored leadership modelled in these two schools transformed the context for effective intercultural, bilingual education. Results point to the importance of leadership by school principals in actualizing the goals set out in Nunavut’s Education Act (2008), governmental mandates, and language laws.